THE BALANCE BEAM AS AN ARTISTIC GYMNASTICS APPARATUS FOR WOMEN: FROM ORIGIN TO CONSOLIDATION - Mauricio Santos Oliveira; Anna Stella Silva de Souza; Andrize Ramires Costa; Myrian Nunomura (University of Ljubljana Press (Založba Univerze v Ljubljani), 2023)
This article seeks to increase the understanding of the historical development of Artistic Gymnastics and, mostly, the women's participation in this sport. Therefore, through historical research, we analyzed the genesis and the inclusion of balance beam apparatus at the core of this gymnastics discipline. The delimitation of the period ranged from 1896 Olympic Games until the years between 1952 and 1964, which are known by the stabilization of the competitive characteristics of Women's Artistic Gymnastics. We observed that in the beginning, as well as in sport in general, women were excluded from this cultural experience. However, throughout history, we observed that the balance beam became a protagonist of the Artistic Gymnastics becoming a stage for reinforcing as much as to confront what women could or could not do in this gymnastics discipline.